Analisis Perputaran Piutang dan Realisasi Pelunasan Piutang pada Distributor Industri Jamu Borobudur Cabang Bogor Tahun 2004 – 2008 - Jeffry . (Jurnal Ilmiah Binaniaga, 2010)
The purpose of this study was to measure the turnover of receivables to total sales by using the ratio of Accounts Receivable and Accounts Receivable Turn Over in Day. By using these ratios can be inferred average receivables turnover and receivables turnover as 1x unknown duration receivables turnover was 353 days. This study also measures the significance of the influence of receivables to cash receipts (cash in ). By looking at the data can be inferred by using simple regression analysis and product moment correlation coefficient ( Pearson ) SPSS Program Version 11:00 regression equation Y = 20911545.008 + 0.358 X, the correlation coefficient of 0.849. This suggests a positive relationship between accounts with cash receipts (cash in ) , categorized by level of relationship is very strong. Based on the hypothesis testing to test whether the effect of X (receivable) to Y (cash receipts) is significant, then the results of the analysis of the test " t " is obtained tcount 12.24 ttable value (0.01) is equal to 2.3264 , this indicates that 12.24 > 2.3264 then t > t table , then the hypothesis that acquired reject H0 and accept H1 (t > t table) means hypothesis test showed a significant effect of receivables to cash receipts (cash in ). From the calculation of correlation coefficient of determination obtained accounts for 72.08 %. A percentage of 27.92 % is due to other factors.